FACTORS THAT INFLUENCE IMPULSIVE BUYING - Asep Kurniawan; Aprillia Verra Puspita (JASS (Journal of Accounting for Sustainable Society), 2021)
This study aims to determine the factors that influence impulsive buying either partially or simultaneously. The data used in this study is primary data by distributing questionnaires in the form of google form. The method used in sampling is probability sampling method with convenience sampling technique and the number of samples in this study were 200 respondents, who were college students and students majoring in accounting in Subang Regency. The data was processed using data quality test methods, different tests, classical assumption tests, multiple regression analysis, and hypothesis testing. The results showed that partially the neuroticism and extraversion variables had a positive and significant effect on impulsive buying. While the mental accounting and conscientiousness variables have no effect on impulsive buying. Simultaneously, the results showed that the variables of mental accounting, conscientiousness, neuroticism, and extraversion simultaneously influenced impulsive buying.